Flood protection at culvert outlets - Stevens, Michael A., author; Watts, Frederick Jay, author; Simons, Daryl B., author; Colorado State University, publisher (Colorado State University. Libraries, 1970)
In this study several classes of information concerning flood protection at culvert outlets are presented. The information is related to the flow conditions at culvert outfalls and to the hydraulics of rigid basins and outlet basins stabilized with rock riprap. In addition, the characteristics of high tailwater and non-scouring, low tailwater basins are covered. In this report it is intended that a hydraulic engineer can take the information contained in the text, examples, illustrations, and figures and apply it toward the design of an energy dissipator of maximum effectiveness. The data on which the report is based were gathered mostly during an experimental program at Colorado State University. In some cases, adequate data were available from other sources. Where such information was needed, it was incorporated into the report.
CER69-70DBS-MAS-FJW4.
Prepared for Wyoming State Highway Department, Planning and Research Division in cooperation with the U.S. Department of Transportation, Federal Highway Administration, Bureau of Public Roads.
Keywords: Culverts -- Design and construction; Flood damage prevention; Roads -- Design and construction